2016
DOI: 10.1108/ilt-03-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analyses of turbulent flow behavior in plain journal bearing

Abstract: Purpose – This paper aims to investigate the fluid flow regime and the elastic effect in a plain cylindrical journal bearing subjected to highly severe operating velocity to better predict the behavior of the bearing for the turbulent flow regime. Design/methodology/approach – A numerical analysis of the behavior of an elastohydrodynamic for cylindrical journal bearing finite dimension coated with antifriction material in turbulent regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Shenoy et al [15] researched the effect of turbulence and misalignment on the steady state characteristics of a centrally loaded single-pad externally adjustable bearing using the Ng-Pan model. Bendaoud et al [16] investigated the turbulent flow pattern and the elastic effect in a journal bearing subjected to high speeds using ANSYS CFX. Lv et al [17] thought that turbulence may locally develop in a large bearing and found that turbulence decreased the speed of the transition from a mixed-lubrication regime to a hydrodynamic lubrication regime.…”
Section: Introductionmentioning
confidence: 99%
“…Shenoy et al [15] researched the effect of turbulence and misalignment on the steady state characteristics of a centrally loaded single-pad externally adjustable bearing using the Ng-Pan model. Bendaoud et al [16] investigated the turbulent flow pattern and the elastic effect in a journal bearing subjected to high speeds using ANSYS CFX. Lv et al [17] thought that turbulence may locally develop in a large bearing and found that turbulence decreased the speed of the transition from a mixed-lubrication regime to a hydrodynamic lubrication regime.…”
Section: Introductionmentioning
confidence: 99%
“…(2006)showedtheeffectofthepressurefieldonthestressdistribution inanuntexturedhydrodynamicjournalbearing.Thisstudyiscarriedoutbysolvingdisplacement equationsusingthefiniteelementmethod.Theirresultsshowthatelasticdeformationsareimportant andpreponderantforhigherrotationalspeeds,andshearstressesareimportantforhigherhydrodynamic pressures. Bendaoud (2014) conducted a search on behavior elastohydrodynamic plain bearing hydrodynamicveryloaded.Theresultsshowthattheheavilyloadedplainbearingspresentsignificant geometricalmodifications.…”
Section: Introductionmentioning
confidence: 99%